The conditional CAPM and cross-sectional evidence of return and beta for Islamic Unit Trust in Malaysia - Ismail, Abd Ghafar; Shakrani, Mohd Saharudin (The International Islamic University Malaysia, 2003)
The aim of this paper is to investigate the relationship between return and beta for Islamic unit trusts using the cross-sectional regression analysis. The estimation of return and beta without differentiating between positive and negative excess market returns produces a flat unconditional relationship between return and beta. Using the conditional CAPM and cross-sectional regression analysis, the evidence in this paper tends to support a significant positive relationship in an up-market and a significant negative relationship in a down-market. This paper suggests that beta could be used as a tool in explaining cross-sectional differences in Islamic unit trusts returns and as a measure of market risk. Based on the adjusted-R and standard error of the conditional relationship between returns we find that beta is higher in a downmarket than in an up-market. Therefore, both statistics are appropriate measurements of conditional relationships.